How New Keynesian Is the US Phillips Curve? - Ragna Alstadheim (Norges Bank, 2013)
I provide a generalization of Calvo price setting, to include non-overlapping contracts as a special case and embed this in a small DSGE model. The resulting Generalized Phillips Curve (GPC) nests New-Keynesian and Neoclassical versions. I linearize the model around a potentially non-zero trend inflation rate, and estimate it on US data using Bayesian methods, allowing for Markov switching in the variances of structural shocks. I find that the Phillips curve is 100% New Keynesian. There is no evidence of either forward or backward indexation. I illustrate that trend inflation affects the estimation of the Phillips curve.
hdl:11250/2496679
Keywords: E13; E31; 330; Phillips curve; neoclassical; indexation; regime-switching; trend inflation